2018
DOI: 10.1186/s12967-017-1374-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of membrane affinity-based method with size-exclusion chromatography for isolation of exosome-like vesicles from human plasma

Abstract: BackgroundPlasma extracellular vesicles (EVs), especially exosome-like vesicles (ELVs), are being increasingly explored as a source of potential noninvasive disease biomarkers. The discovery of blood-based biomarkers associated with ELVs requires methods that isolate high yields of these EVs without significant contamination with highly abundant plasma proteins and lipoproteins. The rising interest in blood-based EV-associated biomarkers has led to the rapid development of novel EV isolation methods. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
415
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(455 citation statements)
references
References 30 publications
36
415
3
1
Order By: Relevance
“…In line with earlier publications, we demonstrate that precipitation- and sedimentation-based isolations co-fractionate significant amounts of serum albumin that mask genuine EV-enriched proteins. Additionally, we herein confirm previous findings [69,83,87] that SEC-based methods represent an efficient way of removing high-abundance serum proteins (Supplemental Figure 6), trading decreased vesicle yield for higher purity [88]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with earlier publications, we demonstrate that precipitation- and sedimentation-based isolations co-fractionate significant amounts of serum albumin that mask genuine EV-enriched proteins. Additionally, we herein confirm previous findings [69,83,87] that SEC-based methods represent an efficient way of removing high-abundance serum proteins (Supplemental Figure 6), trading decreased vesicle yield for higher purity [88]. …”
Section: Discussionsupporting
confidence: 90%
“…These differences might be due to capturing different EV populations or manipulation of originally identical EVs during isolation by aggregation [67] or coating with serum proteins [68]. In line with our findings, Stranska et al recently reported larger particle diameters for EV samples isolated from human plasma by membrane affinity compared to SEC [69]. For most kits, variability of particle diameters was greater in sepsis samples, indicating disease-specific changes in circulating vesicles, or interferences caused by matrix effects in serum from critically ill patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In many instances maintaining the physical integrity of EVs and their surfaces during preparation represents an important pre‐analytical consideration, especially with low abundance material. In this regard, the standard ultracentrifugation methods are often being complemented or replaced by gentler approaches such as density gradient centrifugation, sucrose cushion centrifugation, gel‐permeation chromatography, size‐exclusion chromatography, affinity capture, or microfluidics …”
Section: Challenges and Progress In Ms Of Cancer‐related Extracellulamentioning
confidence: 99%
“…They are suitable for most laboratories and easy to be utility, however, they are costly, especially if a large number of biological samples need to be processed. Besides that, various techniques including filtration [20][21][22], microfluidic-based method [23,24], immuno-affinity and peptide-based isolation [25], size-exclusion chromatography [26][27][28], and so on, have also been proposed for enrichment of exosomes. They have advantages and disadvantages, can be selected according to the experimental command.…”
Section: Introductionmentioning
confidence: 99%